The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.17017/jfish.v2i3.2014.46
|View full text |Cite
|
Sign up to set email alerts
|

Environment and fish fauna of the Atrai River: global and local conservation perspective

Abstract: The fish fauna of the Atrai River were studied for a period of two years from January 2011 to December 2012. Sampling was carried out by several fishing nets and traps on fortnight basis. A total of 74 fish species belonging to 27 families and 52 genera were recorded. Cyprinidae was the most dominant family contributing 18 species in 9 genera. Two alien species were found- Hypophthalmichthys molitrix and Hypostomus plecostomus. Thirty locally threatened species (Vulnerable 13.51%, Endangered 18.92% and Critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 12 publications
5
28
0
Order By: Relevance
“…The number of fish species recorded in the present study (67 species) was found higher than the fish species recorded in the Andharmanik River of Patuakhali district and Bookbhara Baor of Jessore district, where 53 and 38 fish species were found respectively (Mohsin et al 2009. Quite similar number of fish species was recorded from the Halti Beel (63) (Imteazzaman and Galib 2013), Atrai River (74) (Chaki et al 2014) and Padma River (Joadder et al 2015).…”
Section: Figuresupporting
confidence: 65%
See 2 more Smart Citations
“…The number of fish species recorded in the present study (67 species) was found higher than the fish species recorded in the Andharmanik River of Patuakhali district and Bookbhara Baor of Jessore district, where 53 and 38 fish species were found respectively (Mohsin et al 2009. Quite similar number of fish species was recorded from the Halti Beel (63) (Imteazzaman and Galib 2013), Atrai River (74) (Chaki et al 2014) and Padma River (Joadder et al 2015).…”
Section: Figuresupporting
confidence: 65%
“…In a more recent research, Hossain (2014) declared that a total of 30 riverine finfish species have been extinct from Bangladesh. Several research findings confirmed that loss of aquatic biodiversity, in terms of species composition and abundance, is very much conspicuous in the freshwater habitats of Bangladesh, primarily in rivers (Chaki et al 2014;Galib et al 2013;Joadder et al 2015;Mohsin et al 2013Mohsin et al , 2014.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In comparison with present study with Nath (2001), water temperature and salinity were found higher with similar pH but lower DO, total alkalinity and transparency. Similar water quality is also reported in the Atrai River (Chaki et al 2014).…”
Section: Water Quality Parameterssupporting
confidence: 85%
“…Results obtained through studies undertaken by several researchers have revealed same scenario (Galib et al 2009aSamad et al 2010;Chaki et al 2014;Mohsin et al 2013Mohsin et al , 2014Galib 2015;Joadder et al 2015).…”
Section: Catch Analysismentioning
confidence: 69%